Screening athletes for myocarditis with cardiac magnetic resonance imaging after COVID-19 infection - Lessons from an English philosopher - Kim, J. H. (JAMA Cardiology, 2021)
In 1763, Bayes theorem ("An Essay Towards Solving a Problem in the Doctrine of Chances"), one of the most fundamental principles in probability theory, was published in Philosophical Transactions of the Royal Society.1 In a twist of fate, Thomas Bayes had died 2 years prior to the publication of his lasting legacy, which still resonates throughout modern clinical medicine. Bayes theorem is based on conditional probability, or the probability of an event occurring based on other conditions associated with the event in question.1 Today, bayesian philosophy and consideration of pretest probability remains embedded in the determination of best practices for clinical screening and risk stratification.